ответ: x = - 1.
Пошаговое объяснение:
Решим уравнение через дискриминант.
(- x - 4) * (3x + 3) = 0
- 3x² - 3x - 12x - 12 = 0
- 3x² - 15x - 12 = 0
D = b² - 4ac = (- 15)² - 4 * (- 3) * (- 12) = 225 - 144 = 81
x₁ = (- b - √D)/(2a) = (- (- 15) - √81)/(2 * (- 3)) = (15 - 9)/(- 6) = 6/(-6) = - 1
x₂ = (- b + √D)/(2a) = (- (- 15) + √81)/(2 * (-3)) = (15 + 9)/(- 6) = 24/(- 6) = - 4
- 1 > - 4 ⇒ в ответ записываем x = - 1.
Решим уравнение через разложение трёхчлена.
(- x - 4) * (3x + 3) = 0
[ - x - 4 = 0 x₁ = - 4
⇒
[ 3x + 3 = 0 x₂ = - 1
- 1 > - 4 ⇒ в ответ записываем x = - 1.
12/30+5/30+2/30=19/30
10/27-5/8+8/9- общий знаменатель 216
80/216-135/216+192/216=137/216
-1/5+3/10-7/20-общий знаменатель 20
-4/20+6/20-7/40=-5/20=-1/4
-3/20-7/30+2/40-общий120
-18/120-28/120+6/120=-40/120=-1/30
11/60-23/30-17/20-общий 60
11/60-46/60-51/60=-86/60=-43/30=-1 целая13/30